Website Sebagai Alat Promosi Online Dalam Upaya Merekrut CMB Pada Universitas Raharja - Dede Cahyadi; Khanna Tiara; Dhita Rezki Mayosi (UNIVERSITAS RAHARJA, 2020)
In this era of globalization, technology develops increasingly advanced to make it easier for people to do various activities in life, one with the Internet. With the internet everyone can communicate with people who are in different parts of the world. Through this media they can obtain and convey various information needed anytime and anywhere. Nowadays the internet is not only used to obtain information, but it can be used as a medium to do business by building a website. Universities at this time like or dislike should be accustomed to the pattern of promotion online using the website, because the website serves as one of the most efficacious promotional tools and most efficient when compared to Traditional way of marketing. An online system application that can make it easier to convey a large amount of information and feature the superiority of the university is the expected outcome of this research. Nevertheless, the application of this system also still has a lack of facilities and appearance, so it still requires a lot of refinement.